Peran Negara dalam Perlindungan Konsumen Muslim di Indonesia - Mabarroh Azizah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This article aims to describe the state’s role in guaranteeing and protecting Muslim consumers in Indonesia to obtain halal products. This article is a normative legal research which is conducted by exploring principles and norms. The conclusion of this article is that the role of the state in protecting Muslim consumers from prohibited products can be seen from two perspectives, namely the Islamic perspective and the Indonesian constitution perspective. From an Islamic perspective, this protection is obligatory, as well as in the perspective of the Indonesian constitution that the role of the state in facilitating Muslim consumers in obtaining halal products has been described in Article 29 of the 1945 Constitution of the Republic of Indonesia which is a justification of the state's role in ensuring the protection of Muslim consumers from products that are forbidden. This is a public interest to create a welfare state.